Stem Cell Therapy for Thyroid Diseases: Progress and Challenges - Sunyi Ye, Ph.D; Zhu Lixian Zhu, M.D (Elsevier, 2022)
ABSTRACT: Background: Thyroid hormones are indispensable for organ development and maintaining homeostasis. Thyroid diseases, including thyroiditis and thyroid cancer, affect the normal secretion of hormones and result in thyroid dysfunction. Objective: This review focuses on therapeutic applications of stem cells for thyroid diseases. Methods: A literature search of Medline and PubMed was conducted (January 2000-July 2021) to identify recent reports on stem cell therapy for thyroid diseases. Results: Stem cells are partially developed cell types. They have the capacity to form specialized cells. Besides embryonic stem cells and mesenchymal stem cells, organ resident stem cells and cancer stem cells are recently reported to have important roles in forming organ specific cells and cancers. Stem cells, especially mesenchymal stem cells, have anti-inflammatory and anticancer functions as well. Conclusions: This review outlines the therapeutic potency of embryonic stem cells, mesenchymal stem cells, thyroid resident stem cells, and thyroid cancer stem cells in thyroid cells' regeneration, thyroid function modulation, thyroiditis suppression, and antithyroid cancers. Stem cells represent a promising form of treatment for thyroid disorders.